"I was purchasing it; it wasn't given to me": Food project patronage and the geography of dignity work. Issue 3 (16th April 2018) - Bedore, Melanie
Abstract : In response to food access challenges, local organisers are developing community food projects (CFPs) such as good food box programmes, mobile food vending, and non‐profit grocery stores, which (re)introduce affordable retail food options into under‐served communities. This paper explores the patronage of such retail‐based CFPs as dignity work. Whereas Jacobson (e.g., 2009a) elaborates a typology of social processes through which people undertake dignity promotion, this paper re‐examines such processes as personal politics of space. I argue that CFP patronage entails the strategic creation and destruction of physical and symbolic space in order to bring oneself in proximity to, or distance oneself from, morally un/desirable qualities and ways of being. Empirical evidence supporting this interpretation is drawn from mixed methods data collected from patrons and organisers of a Good Food Box programme in south‐eastern Ontario, Canada. The paper concludes with recommendations for supporting food projects' role in protecting, promoting, and restoring their patrons' dignity. It also encourages researchers to engage further with geographical imaginaries to theorise the spatiality of dignity work, building on its relevance to boundary processes, feminist care ethics, and "in the meantime" politics.